ORGANIZATION OF SUMMER HEALTH CARE IN MCT - Xo'jamqulova Zulayho Xolovna (Galaxy International Interdisciplinary Research Journal, 2023)
Summer is the best period for strengthening children's health and developing their physical abilities. In summer health classes, children's health and meaningful leisure activities will be included in the plan.